IMPLEMENTASI TOTAL QUALITY MANAGEMENT PADA PENDIDIKAN JARAK JAUH - Rifqi, Ainur (JURNAL AL-TANZIM, 2018)
Total Quality Management (TQM) in distance education in higher education is rarely developed to improve quality continuously. There are 6 dimensions in TQM, namely leadership, management education, human resource management, information management, customer-centered and satisfaction, and the development of cooperation. College leaders need to create values and goals, and realize objectives through strategies and leadership styles that are suitable to realize the commitment of organizational members..